2012
DOI: 10.1590/s0101-20612012005000119
|View full text |Cite
|
Sign up to set email alerts
|

Effect of starter culture and inulin addition on microbial viability, texture, and chemical characteristics of whole or skim milk Kefir

Abstract: The effect of inulin addition and starters (Kefir grains or commercial starter culture) on the microbial viability, texture, and chemical characteristics of Kefir beverages prepared with whole or skim milk was evaluated during refrigerated storage. The type of starter did not influence microbial viability during the storage of the beverages, but the chemical and textural changes (decreases in pH, lactose concentration, and inulin and increased acidity, firmness, and syneresis) were more pronounced in the formu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
26
1
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 45 publications
(41 reference statements)
9
26
1
8
Order By: Relevance
“…Uraz, Akkuzu, Özcan, and Sevimay (2012) detected C. kefyr and C. famata as the most abundant species in kefir samples. Montanuci, Pimentel, Garcia, and Prudencio (2012) reported that yeast, acetic acid bacteria, and leuconostoc counts at the end of storage had either risen or changed only marginally, while those of LAB and Lactococcus were decreased or changed only marginally compared with those at the beginning of storage. They found that the acidity of kefir fermented with grains increased during storage, whereas no change in acidity was observed in beverages fermented with a starter culture.…”
Section: Microbiological Characteristicsmentioning
confidence: 99%
“…Uraz, Akkuzu, Özcan, and Sevimay (2012) detected C. kefyr and C. famata as the most abundant species in kefir samples. Montanuci, Pimentel, Garcia, and Prudencio (2012) reported that yeast, acetic acid bacteria, and leuconostoc counts at the end of storage had either risen or changed only marginally, while those of LAB and Lactococcus were decreased or changed only marginally compared with those at the beginning of storage. They found that the acidity of kefir fermented with grains increased during storage, whereas no change in acidity was observed in beverages fermented with a starter culture.…”
Section: Microbiological Characteristicsmentioning
confidence: 99%
“…The progressive fermentation of lactose due to active metabolism of the added cultures can result in post acidification reducing the pH (L obato Calleros et al, 2014), which can in turn result in textural changes (Montanuci et al, 2012) and syneresis (L ucey, 2004). Such changes affect negatively the products' quality and reduce it's shelf life (Zhao et al, 2006).…”
Section: Mean Composition and Ph Of Dairy Beveragesmentioning
confidence: 99%
“…In some cases, the increased acidification affected the products' sensory features, reducing their acceptability (Behrens, 2002;Correa et al, 2008) or preference in relation to similar products with a less intense acid taste (Buriti et al, 2008). It is also known that progressive acidification in dairy products can modify their texture throughout the storage (Montanuci et al, 2012). In that manner, it is important to monitor such parameters during the storage of goat whey beverage added of a L. casei strain.…”
Section: Introductionmentioning
confidence: 99%
“…Serum separation occurs as a result of aggregation of protein particles during storage and sedimentation under gravity. Stabilizers, acidity, total solids, milk and culture type can also aff ect the whey leakage in fermented milk beverages (Montanuci et al, 2012). Montanuci et al (2012) observed that an increase of syneresis was noted in kefi rs fermented with kefi r starter culture compared to beverages fermented with kefi r grains.…”
Section: Resultsmentioning
confidence: 99%